A Rare Case of Primary Extranodal Laryngeal Non Hodgkin Lymphoma - P., Mark; A., Najihah Hanim; O., Eshamsol Kamar; A., Suhaila; M., Irfan (IIUM Medical Journal Malaysia, 2018)
Lymphoma is generally a nodal disease and arises from lymphoid tissues or organs. Extranodal lymphoma accounts for almost a third of malignant lymphomas. Squamous cell carcinoma accounts for 90 % of laryngeal carcinoma, while extranodal Non Hodgkin Lymphoma (NHL) attributes only less than 1% of laryngeal neoplasms. Less than 100 of such cases been reported in literature since 1952. As to our best knowledge, no such case was ever reported in our country. We report a case of a 58-year-old gentleman who presented the typical history of laryngeal malignancy however the pathology turned out to be as NHLof Diffuse Large B-cell subtype.